2001
DOI: 10.1097/00062752-200105000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic growth factors in the older cancer patient

Abstract: Aging is associated with a progressive decline in the functional reserve of multiple organ systems, which may lead to enhanced susceptibility to stress such as that caused by cancer chemotherapy. Myelodepression is the most common and the most commonly fatal complication of antineoplastic drug therapy and may represent a serious hindrance to the management of cancer in older individuals. This is already a common and pervasive problem and promises to become more so. Currently 60% of all neoplasms occur in perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 118 publications
0
39
0
2
Order By: Relevance
“…An estimated 60 % of all malignancies occur in patients >65 years of age, and the number of elderly patients with cancer will increase as life expectancy increases and the population ages [1,2]. In the USA, a 67 % increase in the incidence of all cancers is anticipated for older adults (≥65 years of age), and the percentage of all cancers diagnosed in elderly adults is expected to increase from 61 to 70 % by the year 2030 [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated 60 % of all malignancies occur in patients >65 years of age, and the number of elderly patients with cancer will increase as life expectancy increases and the population ages [1,2]. In the USA, a 67 % increase in the incidence of all cancers is anticipated for older adults (≥65 years of age), and the percentage of all cancers diagnosed in elderly adults is expected to increase from 61 to 70 % by the year 2030 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Neutropenia presents an increased risk of serious or life-threatening infections and is a major dose-limiting toxicity for many chemotherapy regimens [4]. Patients aged >65 years are likely to have more comorbidities and take more medications than younger patients, placing them at greater risk than younger patients for developing myelosuppression and neutropenia, the duration of which may reduce survival [1]. Elderly patients are also at increased risk for infections in the presence or absence of neutropenia [2].…”
Section: Introductionmentioning
confidence: 99%
“…1,3 More recently, hematopoietic growth factors have played a major role in preventing infection in cancer patients and shortening the duration of neutropenia in patients receiving chemotherapy. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] As a result, patients can better tolerate the standard chemotherapy regimens and may be able to tolerate the higher doses of chemotherapeutic agents, thereby improving therapeutic outcomes. 3,[9][10][11] During the last decade, numerous clinical trials and meta-analyses have demonstrated the efficacy of colony-stimulating factors (CSFs) in reducing neutropenia and shortening duration of hospitalization among patients with various cancers and all age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Un score de fragilité pathologique (The Groningen Frailty Indicator ≥ 4) augmente la probabilité de décès au cours du traitement [37]. L'anémie est un facteur de risque indépendant de mauvaise tolérance hématologique [38]. L'altération de la fonction rénale [39] et l'hypoalbuminémie peuvent nécessi-ter des adaptations posologiques.…”
Section: éValuation Gériatrique Avant Chimiothérapie Adjuvanteunclassified